Comparison of Different Treatment Protocols in Postmenopausal Osteoporosis - Mehmet Portakal; Zühal E. Altay; Özlem Baysal; Gülsen Aykol; Tülay Öner (Türk Osteoporoz Dergisi, 2005)
This study was planned to compare the effects of three different treatment protocols including calcitonin, calcium and Vit D on bone mineral density (BMD) of postmenauposal women. 90 subjects who were diagnosed as osteoporosis with clinical and laboratory methods were included into the study. The patients were divided into three groups, randomly. Three different treatment protocols (group 1: Calcitonin 200 IU + calcium 1000 mg /day, group 2: Calcitonin 200 IU + calcium 1000 mg/day + calcitriol 0.50 mcg + 1000 mg/day) were administered for a period of 1 year. BMD was measured by the Dual energy X-ray absorbtiometry (DEXA) at the beginning, 6th and 12th months of the study. At the end of 12 months, although, we observed increase in DEXA values of all groups, the only statistically significant increase was observed in group 2 (p<0.05). It is concluded that the treatment protocol including calcitonin, calcitriol and calcium statistically increases BMD.